2013
DOI: 10.1111/ejh.12218
|View full text |Cite
|
Sign up to set email alerts
|

Influence of C‐reactive protein levels and age on the value of D‐dimer in diagnosing pulmonary embolism

Abstract: In the prediction of PE, age and D-dimer levels are relevant, while CRP level is not. Using an age-adjusted D-dimer cutoff in older patients remarkably improves the specificity of D-dimer testing with a minor decline in sensitivity. This may increase the yield of CT-angiography in diagnosing PE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 31 publications
0
7
0
1
Order By: Relevance
“…There is a high incidence rate of deep venous thrombosis (DVT) of lower extremity in China, and the pulmonary thromboembolism formed by detachment of thrombus is the leading cause for death of people (1). Studies have suggested that inflammatory reaction plays a key role in the occurrence and development of DVT, and that inflammatory cytokine is a bioactive peptide that not only acts as a signal transduction factor, but also performs as an effector molecule (2).…”
Section: Introductionmentioning
confidence: 99%
“…There is a high incidence rate of deep venous thrombosis (DVT) of lower extremity in China, and the pulmonary thromboembolism formed by detachment of thrombus is the leading cause for death of people (1). Studies have suggested that inflammatory reaction plays a key role in the occurrence and development of DVT, and that inflammatory cytokine is a bioactive peptide that not only acts as a signal transduction factor, but also performs as an effector molecule (2).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed a correlation between hs-CRP and D-dimer in patients with pulmonary embolism 29 . According to our research, a stronger baseline correlation was found between hs-CRP and D-dimer than between hs-CRP and fibrinogen in the males as baseline.…”
Section: Discussionmentioning
confidence: 97%
“…1,2 Age, active malignancy, infection, pregnancy and use of anticoagulants are well known to have an influence on D-dimer levels. [3][4][5][6] Use of medication with an effect on thrombus formation, such as HMG-CoA reductase inhibitors, more commonly known as statins, may influence D-dimer levels as well. These antithrombotic properties are part of what has been referred to as the cholesterol-independent or "pleiotropic" effects of statins, explaining why the benefits observed with statins appear to exceed what might be expected from changes in cholesterol levels alone.…”
Section: Introductionmentioning
confidence: 99%